2021
DOI: 10.3389/fvets.2021.662887
|View full text |Cite
|
Sign up to set email alerts
|

Semen Quality and Freezability Analyses in the Ejaculates of Two Poitou Donkeys in the Southern Hemisphere

Abstract: The Baudet du Poitou is a vanishing donkey breed recognized for engendering robust working mules. In Chile, only two pure breed Poitou males exist, which belong to the Chilean army and are used for mule production. We performed an extensive sperm and seminal analysis of these two jackasses aged 3 and 6 years and investigated the use of a simple hypometabolic extender for sperm cryopreservation. Computer-assisted sperm analysis showed high motility, velocity, and linearity in sperm movement. The seminal plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…For example, the age of sexual maturity in pigs is approximately between 5 and 8 months, while in cattle, it is between 10 and 18 months. Horses and donkeys require 18 to 24 months; sheep and goats need 6 to 10 months; camels take 24 to 36 months; and rabbits mature relatively early, needing only 3 to 4 months [ 40 , 41 , 42 , 43 , 44 , 45 ]. However, as a primitive local breed that gradually formed under natural grazing conditions in alpine regions, the sexual maturation process of the Mongolian horse is influenced by various factors, including the environment and nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the age of sexual maturity in pigs is approximately between 5 and 8 months, while in cattle, it is between 10 and 18 months. Horses and donkeys require 18 to 24 months; sheep and goats need 6 to 10 months; camels take 24 to 36 months; and rabbits mature relatively early, needing only 3 to 4 months [ 40 , 41 , 42 , 43 , 44 , 45 ]. However, as a primitive local breed that gradually formed under natural grazing conditions in alpine regions, the sexual maturation process of the Mongolian horse is influenced by various factors, including the environment and nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Ortiz et al (2015) reported a seminal quality index of 0.65 ± 0.3 in thawed Andalusian donkey semen, being a higher value than those found in the present research for all treatments. This could be due to the fact that post‐thaw semen quality and sperm freezability seem to vary consistently among donkeys (Ortiz et al, 2015) and aspects such as breed, age, seasonality and frequency of collections, affect this variability (Carluccio et al, 2013; Ebel et al, 2021). In addition, the freezing protocol used by Ortiz et al (2015), as well as the sperm quality parameters used to calculate the seminal quality index, were different from the present study, which could generate different results.…”
Section: Discussionmentioning
confidence: 99%